2009
DOI: 10.1306/02180908080
|View full text |Cite
|
Sign up to set email alerts
|

Structural and diagenetic control of fluid migration and cementation along the Moab fault, Utah

Abstract: After research positions at Stanford University and the Monterey Bay Aquarium Research Institute, he joined the Bureau of Economic Geology at the University of Texas in Austin in 2006. His research interests include the interaction of brittle deformation and diagenesis, and fault and fracture mechanics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
126
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(133 citation statements)
references
References 68 publications
6
126
0
Order By: Relevance
“…Displacements along faults can result in a high fracture density around and between faults, creating a damage zone that has the potential to increase the fluid flow due to enhanced permeability. The key factors for the increase in fracture density are the change in mechanical rock properties, interactions between faults and a change in fault geometry (Bolas and Hermanrud, 2003;Gartrell et al, 2004;Leckenby et al, 2005;Eichhubl et al, 2009;Kim and Sanderson, 2010;Ziesch, 2016). The S H -wave reflection-seismic profiles carried out in this study identified a complex local and regional fault system with a dense fracture network, which enables the groundwater to circulate through the evaporites and therefore it enhances dissolution and subsidence due to an increase in permeability.…”
Section: Releasing Bendmentioning
confidence: 81%
“…Displacements along faults can result in a high fracture density around and between faults, creating a damage zone that has the potential to increase the fluid flow due to enhanced permeability. The key factors for the increase in fracture density are the change in mechanical rock properties, interactions between faults and a change in fault geometry (Bolas and Hermanrud, 2003;Gartrell et al, 2004;Leckenby et al, 2005;Eichhubl et al, 2009;Kim and Sanderson, 2010;Ziesch, 2016). The S H -wave reflection-seismic profiles carried out in this study identified a complex local and regional fault system with a dense fracture network, which enables the groundwater to circulate through the evaporites and therefore it enhances dissolution and subsidence due to an increase in permeability.…”
Section: Releasing Bendmentioning
confidence: 81%
“…Fault zones in high-porosity siliciclastic rocks exhibit cataclastic fault cores with permeabilities reduced by up to 2-3 orders of magnitude (Balsamo and Storti 2010). Damage-zone permeability is influenced and governed by deformation-band networks, that display zones of reduced permeability (Rath et al 2011;Storti et al 2003), and fractures that enhance damage-zone permeability (Eichhubl et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Diagenesis and cementation also exert a control on the mechanical and fluid flow properties of fault zones (Knipe, 1993;Eichhubl and Boles, 2000;Boles et al, 2004;Rawling et al, 2001;Eichhubl et al, 2009;Laubach et al, 2010). During diagenesis, the development of quartz cements may greatly increase the mechanical strength of sandstones through the formation of intergranular bonds (Dvorkin and Yin, 1995;Hiatt et al, 2007;Cook et al, 2011Cook et al, , 2015 that promote a transition from deformation band to transgranular fracture formation during faulting (Davatzes et al, 2003(Davatzes et al, , 2005Johansen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%